Study on fracture behavior in stiff-thin-film-on-soft-substrate structures under biaxial stress state. (1st June 2021) - Li, Jun; Li, Chuanwei; Li, Linan; Wang, Qi; Wang, Zhiyong; Wang, Shibin; Sun, Cuiru
Abstract: The fracture behavior in stiff-thin-film-on-soft-substrate structures (STFSS) differs significantly from that in bulk materials, and has thus become a hot spot in solid mechanics and materials. Traditional research on the fracture mechanics in STFSS mostly focuses on the mechanical behavior under uniaxial stress state. However, in actual applications, STFSS is subjected to biaxial loading. In response to this lack of research, the present work examined the fracture behavior in STFSS under biaxial stress state by using a self-developed biaxial tension rig. Specially designed and fabricated STFSS specimens with prefab cracks along desirable directions were employed. The influence of the biaxial loading ratio and the prefab cracks on STFSS fracture behavior has been analyzed and discussed both theoretically and experimentally. The experimental results agree well with the theoretical model, which validates the feasibility of the current investigation for STFSS.